Attaining New Knowledge on Inclusive Education: A Case Study of Students' Voices - Jorun Buli-Holmberg; Leda Kamenopoulou (Athens Institute for Education and Research, 2017)
The purpose of this research was to gather the voices of students undertaking a Master's programme on Special and Inclusive Education by exploring their perceptions of what they have learned about inclusive education during the programme. We used the case study approach in order to investigate the students' perceptions and reflections on their learning outcomes related to how they understand inclusive education, with specific focus on the students' awareness of change, how they understand the principle of inclusion and their explanations of inclusive education. Ten students participating in the Master's programme took part in the study. Data were collected with an open-ended questionnaire tool that students completed half way in their studies. Students' qualitative statements were analysed through an inductive approach and three main themes emerged: "understanding of inclusive education" "awareness of change", and "success criteria for practicing inclusive education". Results suggest that the student group as a whole considered that they had attained new knowledge, expanded and nuanced their understanding of inclusive education, and the majority of the students were aware of how they had enriched their knowledge and were able to state how they will go about implementing inclusive education in practice.